2020
DOI: 10.1002/fsn3.2066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enzymatic treatments on the hydrolysis and antigenicity reduction of natural cow milk

Abstract: Cow milk (CM) allergy is one of the most common food allergies worldwide; the most abundant CM proteins, such as casein (CN), β‐lactoglobulin (β‐LG), and ɑ‐lactalbumin (ɑ‐LA), are all potentially allergenic. Reducing the antigenicity of CM continues to be a major challenge. However, previous studies have focused on the antigenicity of individual allergic CM proteins. Thus, in the present study, we aimed to evaluate the effects of different food‐grade enzymes on the antigenicity of CN, β‐LG, ɑ‐LA in natural CM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 53 publications
(42 reference statements)
5
31
0
Order By: Relevance
“…Samples were prepared as previously described (Liang et al, 2021). Briefly, enzyme solutions (0.1 g/mL) were prepared with Alcalase, Protamex, Flavourzyme, Neutrase, papain, and pepsin, respectively.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples were prepared as previously described (Liang et al, 2021). Briefly, enzyme solutions (0.1 g/mL) were prepared with Alcalase, Protamex, Flavourzyme, Neutrase, papain, and pepsin, respectively.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…The IgE binding capacity of CM and HM was further analyzed using western blotting, which referenced the method reported previously by Liang et al (2021). Briefly, protein content of samples was detected and separated with SDS-PAGE.…”
Section: Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that cow’s milk is a significant nutritional supplement in life, while also being one of the eight food allergens [ 1 ]. Cow’s milk allergies are especially common in infancy and childhood, with symptoms such as vomiting and diarrhea., and can be life-threatening when severe [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of enzyme preparations (EPs) of animal, plant and microbial origin are used for the whey proteins hydrolysis. Studies have shown the potential for the use of bacterial serine proteases (EC 3.4.21.62) -EP Alcalase (Novozymes A/S) and a complex preparation of fungal exo-and endopeptidases with high leucine aminopeptidase activity -Flavourzyme (Novozymes A/S) in whey protein hydrolysis [7,10]. The best results were obtained when using a two-stage sequential treatment of milk protein concentrate with Alcalase and Flavourzyme [11].…”
Section: Introductionmentioning
confidence: 99%